2017
DOI: 10.3892/mmr.2017.7096
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 treatment attenuates high glucose-induced peritoneal epithelial to mesenchymal transition in mice

Abstract: It has been previously demonstrated that 1,25(OH)2D3 prevents the progression of epithelial to mesenchymal transition (EMT). However, it remains unclear whether 1,25(OH)2D3 has a role in peritoneal EMT stimulated by high glucose (HG) peritoneal dialysis fluid (PDF). The present study was performed to investigate the role of 1,25(OH)2D3 in the progression of EMT in the peritoneal mesothelium. A total of 35 male Kunming mice were randomly assigned into seven groups. In the control group, no diasylate or saline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Oral rapamycin, which inhibits mTOR, has been shown to reduce peritoneal thickening, inflammation, angiogenesis, and lymphangiogenesis by the blockade of HIF-1α, TGF-β1 and VEGF in murine models of PD induced EPS [46]. Other drugs that have been proposed in EPS treatment include mycophenolate mofetil, colchicine, azathioprine, angiotensin converting enzyme inhibitors/angiotensin II receptor blockers, calcitriol, benfotiamine, thalidomide and dipyramidole [46,58,[127][128][129][130]. The use of non-steroidal immunosuppressants (azathioprine, mycophenolate mofetil, rapamycin), with or without glucocorticoids, may improve EPS, but there are no clinical trials and effectiveness is based on case reports [124].…”
Section: Tamoxifen and Ragementioning
confidence: 99%
See 1 more Smart Citation
“…Oral rapamycin, which inhibits mTOR, has been shown to reduce peritoneal thickening, inflammation, angiogenesis, and lymphangiogenesis by the blockade of HIF-1α, TGF-β1 and VEGF in murine models of PD induced EPS [46]. Other drugs that have been proposed in EPS treatment include mycophenolate mofetil, colchicine, azathioprine, angiotensin converting enzyme inhibitors/angiotensin II receptor blockers, calcitriol, benfotiamine, thalidomide and dipyramidole [46,58,[127][128][129][130]. The use of non-steroidal immunosuppressants (azathioprine, mycophenolate mofetil, rapamycin), with or without glucocorticoids, may improve EPS, but there are no clinical trials and effectiveness is based on case reports [124].…”
Section: Tamoxifen and Ragementioning
confidence: 99%
“…The activation of vitamin D receptors has been shown to reduce inflammation and fibrosis in EPS and also acute/chronic pancreatitis [130,157]. This is related to the inhibition of TGF-β1/SMAD signaling by genomic competition, and the blockade of NF-κB activation and p65/p50 nuclear translocation.…”
Section: Vitamin D Receptor Agonistsmentioning
confidence: 99%
“…In PD patients, the data regarding the effect of vitamin D analogues on OS are scarce and only derived from experimental studies. In vitro as well as in vivo studies in mice showed that the active form of vitamin D inhibited accumulation of free radicals and glycoxidation and therefore might preserve the peritoneum homeostasis, through amelioration of OS status [107109].…”
Section: Exogenous Antioxidant Supplementation In Hd and Pd Patientsmentioning
confidence: 99%
“…Vitamin D analogs can suppress matrix-producing myofibroblast activation by upregulating the expression of anti-fibrotic hepatocyte growth factor in renal interstitial fibroblasts [ 123 ]. In human peritoneal mesothelial cells, inhibitory effects of VDR agonists on EMT have also been reported [ 124 , 125 ].…”
Section: Renoprotective Mechanisms Of Vdrmentioning
confidence: 99%